Hedonic Evaluation of Randang Quality from Two Restaurants in Padang City - Arsyad Athari; Elida; Lucy Fridayati; Juliana Siregar (Universitas Negeri Semarang, 2025)
Randang is a traditional Minangkabau dish that is popular for its distinctive flavour which is produced by a long cooking process using strong spices and herbs. This popularity has made it a must-have dis in various restaurants. Each restaurant serves Randang with different characteristics, thus influencing variations in consumer preferences. This study aims to analyze differences in the level of preference of culinary arts students for Randang from two restaurants in Padang City, namely Rajo-rajo and Selamat. The study used a quantitative method with a comparative approach. A total of 50 culinary arts students served as panelists in a hedonic test using a scale of 1-7. Data were analyzed using a Paired Sample t-Test with SPSS 26. The results showed significant differences in dadak color (P=0.004), meat texture (P=0.000), and the dadak taste (P=0.011). Overall, panelists preferred Randang from Rajo-rajo restaurant over Selamat restaurant. Sensory characteristics were proven to influence the level of student preference for Randang. These findings provide understanding for culinary entrepreneurs about consumer preferences for Randang and serve as a basis for developing culinary products based on cultural heritage.